2021
DOI: 10.1101/2021.06.29.450340
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HMMploidy: inference of ploidy levels from short-read sequencing data

Abstract: The inference of ploidy levels from genomic data is important to understand molecular mechanisms underpinning genome evolution. However, current methods based on allele frequency and sequencing depth variation do not have power to infer ploidy levels at low- and mid-depth sequencing data, as they do not account for data uncertainty. Here we introduce HMMploidy, a novel tool that leverages the information from multiple samples and combines the information from sequencing depth and genotype likelihoods. We demon… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 69 publications
(108 reference statements)
0
4
0
Order By: Relevance
“…Nucleotide, genotype and allele frequency likelihoods ngsJulia provides utilities to calculate nucleotide and genotype likelihoods, i.e. the probability of observed sequencing data given a specific nucleotide or genotype, 21 for an arbitrary ploidy level, as in Soraggi et al 22 We now describe how such quantities are calculated in ngsJulia.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nucleotide, genotype and allele frequency likelihoods ngsJulia provides utilities to calculate nucleotide and genotype likelihoods, i.e. the probability of observed sequencing data given a specific nucleotide or genotype, 21 for an arbitrary ploidy level, as in Soraggi et al 22 We now describe how such quantities are calculated in ngsJulia.…”
Section: Methodsmentioning
confidence: 99%
“…Following the notation in Soraggi et al, 22 for one sample and one site, we let O be the observed NGS data, Y the ploidy, and G the genotype. Therefore, G has values in 0, 1,…, Y f g , i.e.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations